Problematika Shadow Teacher Dalam Membantu Proses Pembelajaran Pendidikan Agama Islam Bagi Anak Berkebutuhan Khusus di SD Lebah Pembelajar - Fathiyyah Putri Pasaribu; Salmi Wati; Charles Charles (Pusat Riset dan Inovasi Nasional, 2023)
Based on observations that have been made by researchers at Lebah Pembelajar Mandiangin Koto Selayan Elementary School, it shows that in helping the learning process of Islamic Religious Education for children with spesial needs there are problems in it. The purpose og this researchh is to find out that problems a shadow teacher experienced. This research is a descriptive qualitative research with interviews, observation and documentation. Data collection techniques, data reduction, data presentation and conclusion. Based on the result of the research that has been done, it can be concluded that shadow teacher experience problem in helping chidren with spesial needs, namely the problem of providing material, achieving learning objective, giving motivation, supervising the concentartion of children, controlling children’s behavior and problem in collaborating with parent of children with special needs, the efforts made and the importance of establising good cooperation and communication in very obstacle experienced, namely cooperation with the homeroom teacher of class 4. Islamic religious education subject teachher, the principal and of course communication related to the child’s problems to the child’s parents.